A REVIEW ON FERMENTED FISH: MICROBIOLOGY, CHEMISTRY AND HEALTH BENEFITS - Madhumita Mondal; Souvik Tewari; Poulami Adhikary Mukherjee; Ranajit Kumar Khalua (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Traditional food preservation techniques like fermentation are frequently employed to increase food safety, shelf life, and organoleptic and nutritional qualities. Fish that has been fermented is produced, eaten, and an essential component of many food traditions across the world. Additionally, fish fermentation is a major industry in many nations and a source of fascinating bacteria. This review tries to update microbiology, chemistry and health benefits of fermented fish